A SCOR based approach for measuring a benchmarkable supply chain performance - Kocaoglu, Batuhan; Gulsun, Bahadir; Tanyas, Mehmet (SPRINGER, 2013)
Performance measurement can only help to identify the problems existing in the current supply chain, while it is helpless in exploring the root causes of these problems and thus choosing corresponding actions to improve supply chain performance. The conflict between the top-down strategy decomposition and the bottom-up implementation process is serious. Therefore, in order to overcome the above issues, it is very necessary to link strategic objectives to operations, which could help managers, especially those operating at a strategic level, to know more operational mechanism of supply chains. In this study, an integrated approach which employs analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) together is proposed for the linking strategic objectives to operations. Supply chain operations reference model is used to model the linkage of the strategic objectives and operational metrics in a hierarchical way. The AHP is used to analyze this metric hierarchy and determine weights of the metrics, and TOPSIS method is used to make a normalization of metric values having different units, so a comparison will be available. Proposed approach is applied to a problem of decision making process in a manufacturing company. Company managers found the application and results satisfactory and implementable in their decisions.
Keywords: Supply chain management; Performance measures; SCOR model; AHP; TOPSIS; Normalization; ANALYTICAL HIERARCHY PROCESS; BALANCED SCORECARD; SELECTION; MANAGEMENT; PRIORITIES; FRAMEWORK; Computer Science; Engineering